2022
DOI: 10.3389/fphar.2022.849074
|View full text |Cite
|
Sign up to set email alerts
|

Tianma Gouteng Decoction Exerts Pregnancy-Protective Effects Against Preeclampsia via Regulation of Oxidative Stress and NO Signaling

Abstract: Preeclampsia (PE), a pregnancy-specific syndrome with the major molecular determinants of placenta-borne oxidative stress and consequently impaired nitric oxide (NO) generation, has been considered to be one of the leading causes of maternal morbidity as well as mortality and preterm delivery worldwide. Several medical conditions have been found to be associated with increased PE risk, however, the treatment of PE remains unclear. Here, we report that Tianma Gouteng Decoction (TGD), which is used clinically fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…CCK‐8 assays were performed to determine cell viabilities as described previously 16 . Briefly, cells at 80% confluence were re‐seeded into 96‐well plates and were transfected with ALKBH1‐expressing plasmid, ALKBH1‐shRNA, GPR137‐shRNA or control vectors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…CCK‐8 assays were performed to determine cell viabilities as described previously 16 . Briefly, cells at 80% confluence were re‐seeded into 96‐well plates and were transfected with ALKBH1‐expressing plasmid, ALKBH1‐shRNA, GPR137‐shRNA or control vectors.…”
Section: Methodsmentioning
confidence: 99%
“…Isolation of total RNA from RCC cell lines, Caki-1, 786-O, ACHN, Osrc2, A498 and 769-P, was conducted with a TRIzol reagent (Takara Biotechnology, Beijing, China) according to the manufacturer's protocol as described previously. 16 For generating first-strand cDNA, 5 μg total RNA in a volume of 20 μL was reversely transcribed by using SuperScript III reagent (Life Technologies) and the oligo-(deoxythymidine) primer with incubation at 42°C for 1 h. Subsequently, the mRNA expression of target genes was measured by qRT-PCR experiments with the synthesized cDNA. The relative amounts of the mRNA expression of the target genes were normalized to the corresponding GAPDH levels, respectively, and consequently, the relative difference in mRNA expression was calculated by 2 −ΔΔCt method as described previously.…”
Section: Total Rna Isolation Reverse Transcription and Quantitative R...mentioning
confidence: 99%
See 1 more Smart Citation
“…Vaginal smears were daily obtained from female mice until the smears showed that they were oestrous. A PE mouse model was induced by subcutaneous injection of L-NAME [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The PE rat model was established by subcutaneous injection of NG-nitro-L-arginine methyl ester (L-NAME). 32,33 Different working groups have previously established the PElike model that has been used in this study. [34][35][36] It is induced by the administration of L-NAME, which is an inhibitor of NO production, as it inhibits the NOS enzyme, prevents endothelium-dependent relaxation, and produces an increase in the blood pressure.…”
Section: Animal Modelmentioning
confidence: 99%